Pharmacokinetics of piperaquine transfer into the breast milk of Melanesian mothers - Moore, B.; Salman, S.; Benjamin, J.; Page-Sharp, Madhu; Yadi, G.; Batty, Kevin; Siba, P.; Mueller, I.; Davis, T. (American Society for Microbiology, 2015)
Transfer of piperaquine (PQ) into breast milk was examined in 27 Papua New Guinean women given a 3-day course of dihydro-artemisinin-PQ or sulfadoxine-pyrimethamine-PQ during the second/third trimester. Breast milk was sampled on days 1, 2, 3 to 5, 7 to 11, and 14 to 17 postdelivery, a median of 70 days postdose (range, 6 to 145 days). A blood sample was taken at delivery, and additional serial samples were available from 9 women who delivered within 42 days of dosing. Milk and plasma PQ were assayed by high-performance liquid chromatography. A population-based approach was used to model the loge(plasma) and milk concentration-time data. A sigmoid Emax model best described PQ breast milk transfer. The population average milk: plasma PQ ratio was 0.58, with a peak of 2.5 at delivery. The model-derived maximum milk intake (148 ml/kg of body weight/day) was similar to the accepted value of 150 ml/kg/day. The median estimated absolute and relative cumulative infant PQ doses were 22 µg and 0.07%, respectively, corresponding to absolute and relative daily doses of 0.41 µg/kg and 0.004%. Model-based simulations for PQ treatment regimens given at birth, 1 week postdelivery, and 6 weeks postdelivery showed that the highest median estimated relative total infant dose (0.36%; median absolute total dose of 101 µg/kg) was seen after maternal PQ treatment 6 weeks postpartum. The maximum simulated relative total and daily doses from any scenario were 4.3% and 2.5%, respectively, which were lower than the recommended 10% upper limit. Piperaquine is transferred into breast milk after maternal treatment doses, but PQ exposure for suckling infants appears safe.